5-ALA-guided resection of glioblastoma: a single-centre, retrospective analysis of progression pattern and survival. (31st January 2018) - Senthil, Keerthi; Piper, Rory J; Sage, William; Sinha, Rohit; Jena, Raj; Price, Stephen
Abstract: INTRODUCTION: The EORTC-NCIC trial in glioblastoma showed a median overall survival (OS) rate of 14.6 months following resection and chemoradiotherapy. This poor prognosis is attributed to early invasion and almost inevitable progression with failure to achieve local control. However, improvement in progression-free survival (PFS) has been shown in the use of 5-aminolevulinic acid (5-ALA), a fluorescent agent which accumulates in tumour cells. It has been adopted as an intraoperative tool to enhance the identification of the tumour-brain boundary, even beyond contrast enhancement on preoperative MRI, and thus aims to improve local control. However, it is not yet evident if 5-ALA alters pattern of progression. We therefore investigated the survival and progression patterns of glioblastoma after 5-ALA-guided resection. METHOD: We retrospectively identified all glioblastoma patients who underwent 5-ALA-guided resection between 2009–2014 and received chemoradiotherapy. PFS and OS were analysed using Kaplan-Meier and log-rank tests. Progression pattern was classified as local (<30mm from the resection margin) or distal. RESULTS: We identified 157 patients. OS was significantly longer in those with complete versus incomplete resection (median survival of 16.9 vs. 13.9 months; p=0.013; n=153). PFS was not significantly different between the groups (11.5 vs 7.5 months; p=0.118). 85 patients had available follow-up MRI with evidence of progression. 55/85 (66%) had complete and 30/85 (34%) had incomplete resections. Of those that relapsed after complete resection only 3/55 (5%) patients had at least one distal lesion. In contrast, after incomplete resection, 3/30 (10%) had distal relapse. CONCLUSION: From our 5-ALA cohort, we have found comparable median OS rates to the EORTC-NCIC trial. We confirm a significant improvement in OS in complete than in incomplete resection. Despite using 5-ALA, and compared to other non-5-ALA studies, we have not been able to show better local control or any change to rate of distant progression.